Constitutionalization of Commercial Law - Landa Arroyo, César (2015)
The Constitution, being the Supreme Law of the Peruvian legal system, irradiates its normative force towards all the legal fields. For its part, Commercial Law is an area based on privatea utonomy; however, in our legal system a zone free of constitutional control does not exist.In this article, the author conducts a remarkable analysis about the constitutionalization of Commercial Law, making reference to the Constitutional Court’s jurisprudence which, applying fundamental principles  and  rights,  has had an effect on the application of the commercial laws in our country.